Study on Explosion-Resistance of Biomimetic Layered Honeycomb Structure. (19th February 2020) - Li, Ji; Shi, Shaoqing; Luo, Weiming; Wang, Qifan
Abstract : A new type of explosion-resistant biomimetic layered honeycomb structure was designed based on the natural mechanism and biological inspiration, which was mainly composed of a sacrificial layer and a bearing layer. The shock tube device was adopted to analyze the dynamic response of the biomimetic layered honeycomb structure under the action of explosion load in order to obtain the deformation modality, deflection data, and strain time-history curve of the structure. It turns out that the maximum deformation deflection of the back panel of the structure is only 28 mm. Compared with the structure of single-layer honeycomb, the independent sacrificial layer, and bearing layer, the biomimetic layered honeycomb structure has good explosion-resistant performance and can repeatedly bear multiple explosion loads. Besides, equivalent homogenization theory was employed to carry out numerical simulation. The results show that the numerical simulation results are perfectly in line with the results of experiments, and the numerical simulation method is proven to be feasible and effective. Under the action of explosion load, the biomimetic layered honeycomb structure absorbs energy mainly by sacrificial layers that are in layered and staggered arrangement. In addition, the sharp rangeability of the kinetic energy of bearing layer structure indicates that it has the feature of large mass, which can be used as the bearing part of the biomimetic layered honeycomb structure.